2014
DOI: 10.1007/s10965-014-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of sustained release drug-loaded nanofibers of cellulose acetate and ethyl cellulose polymer blends prepared by electrospinning and their in-vitro drug release profiles

Abstract: Sustained release cellulose acetate (CA) and ethyl cellulose (EC) polymer blend nanofibers loaded with ketoprofen (KET) were successfully prepared by electrospinning. Successful fiber formation has been investigated by using two different binary solvent systems, i.e., acetic acid + distilled water (2:1 v/v) and acetone + N,N-DMAc + ethanol (2:1:1 v/v). Scanning electron microscopy (SEM) images showed that morphological features gradually change as the ratio of both polymers change. Nanofiber diameter also decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…For the fibers loaded with vitamins, again no Bragg reflections can be observed in the XRD patterns, demonstrating that VE was rendered amorphous by the electrospinning process. These results agree with the literature [34][35][36][37] . It has been reported that the very rapid solvent evaporation which occurs during electrospinning prevents crystallization from occurring, because there is insufficient time for the molecular rearrangement required for development of a crystal lattice.…”
Section: Further Characterizationsupporting
confidence: 94%
“…For the fibers loaded with vitamins, again no Bragg reflections can be observed in the XRD patterns, demonstrating that VE was rendered amorphous by the electrospinning process. These results agree with the literature [34][35][36][37] . It has been reported that the very rapid solvent evaporation which occurs during electrospinning prevents crystallization from occurring, because there is insufficient time for the molecular rearrangement required for development of a crystal lattice.…”
Section: Further Characterizationsupporting
confidence: 94%
“…Therefore, it is widely used in nanofibers preparation, either blended or coaxial electrospun, for application in drug-release fields. [29] Hu et al have employed the blended electrospun of PNIPAAm and EC to prepare nanofibers for delivering drug. This delivery system has advantages in drug sustained release and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The EC that belongs to biologic materials has been recognized as an excellent wall material in the preparation of microcapsule, as well as drug carriers. 18,19 The features of low-cost, good compatibility and great chemical stability make it a promising choice to be used as frame in the binary binder systems with GAP. In theory, the combination of EC and GAP will produce a stable structure in the nal product.…”
Section: Ink Formulations and Inkjet Printingmentioning
confidence: 99%